Ribotype differences between clinical and environmental isolates of Burkholderia pseudomallei. - Trakulsomboon, S; Dance, D; Smith, MD; White, N; Pitt, T (1997)
Burkholderia pseudomallei is isolated frequently from the soil in regions where the disease melioidosis occurs. However, recent surveys in Thailand have shown that the frequency of isolation of the organism from soil samples is not directly related to the incidence of melioidosis in an area. To determine whether strain populations of B. pseudomallei prevalent in soil are gentypically related to strains causing clinical disease, rRNA BamHI restriction fragment length polymorphisms (RFLP) of 139 soil environmental isolates and 228 human isolates were compared. Two groups of ribotype patterns were found. Group I comprised 37 different ribotype patterns which were characterised by five to eight hybridisation bands of 2.8- > 23 kb. All of these ribotypes were identified among the clinical isolates, and 18 of them were also found in 59 environmental isolates. Group II was represented by 12 ribotypes found only in environmental strains. These ribotype patterns comprised one to five bands in the size range 9- > 23 kb. All but one of the 73 isolates in this group grew on a minimal medium supplemented with L-arabinose. In contrast, only 3% of the 66 isolates from the environment with group I ribotype patterns could utilise this sugar as their sole energy source. These findings suggest that B. pseudomallei strains that utilise arabinose constitute a population that is genetically distinct from other environmental and clinical strains.